2015
DOI: 10.1103/physrevd.91.123512
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the large scale volume weighted halo velocity bias in simulations

Abstract: A profound assumption in peculiar velocity cosmology is bv = 1 at sufficiently large scales, where bv is the volume weighted halo(galaxy) velocity bias with respect to the matter velocity field. However, this fundamental assumption has not been robustly verified in numerical simulations. Furthermore, it is challenged by structure formation theory (BBKS, 1986, ApJ; Desjacques and Sheth, 2010, PRD), which predicts the existence of velocity bias (at least for proto-halos) due to the fact that halos reside in spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…This will then allow us to measure the real halo velocity bias, free of otherwise severe systematic error from the sampling artifact. We will present such measurements in [5], which belongs to our ongoing efforts toward understanding the velocity field, redshift shift space distortion, and velocity reconstruction in spectroscopic redshift surveys [12,24]. The current paper focuses on the sampling artifact in the gradient part of the velocity field.…”
Section: Self-calibration and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will then allow us to measure the real halo velocity bias, free of otherwise severe systematic error from the sampling artifact. We will present such measurements in [5], which belongs to our ongoing efforts toward understanding the velocity field, redshift shift space distortion, and velocity reconstruction in spectroscopic redshift surveys [12,24]. The current paper focuses on the sampling artifact in the gradient part of the velocity field.…”
Section: Self-calibration and Discussionmentioning
confidence: 99%
“…The existence of a sampling artifact in the volume weighted velocity power spectrum has been realized in simulations [5,12,13] for both the DM and halo velocity fields. These works found that its impact increases with decreasing number density.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent years many studies have attempted to measure this velocity bias and its effect by comparing the velocity divergence power spectrum measured from simulated halos and the corresponding dark matter field (de la Torre & Guzzo 2012; Elia et al 2012;Jennings et al 2015;Zheng et al 2015), however the magnitude of this effect remains largely uncertain due to numerical resolution issues and difficulties in measuring the velocity divergence power spectrum. Regardless, most studies agree that the effect of the velocity bias is small for k < 0.1 h Mpc −1 , and hence one could argue that it remains unimportant for current measurements of the growth rate of structure from peculiar velocities, which relies primarily on the information from linear scales.…”
Section: γ Parameterisationmentioning
confidence: 99%
“…It consists of two parts, halo velocity bias b v and halo density bias b h . Prior to this study, the detailed investigation on halo velocity bias has been made [104,105]. In [105], authors provided an accurate fitting formula of b v at k 0.25 h Mpc −1 , valid for various halo mass bins at different redshifts.…”
Section: Introductionmentioning
confidence: 99%